Drawings to explore faculties' and students' perceptions from different generations cohorts about dental education: A pilot study - Renata Grazziotin-Soares; Diego Machado Ardenghi (Nature Publishing Group, 2022)
Abstract Introduction/Aims We aimed at using drawings as a form of data collection to give voice to older and younger generations in regards to educational practices in undergraduate dentistry. Materials and methods First year dental students (younger generations) and faculty members (older generations) produced drawings depicting their perceptions of the current dental education learning environment. Qualitative analysis was conducted independently by two researchers using the drawings to produce codes, categories and themes. Results 15 drawings were produced: 9/34 (26.4%) made by students and 6/20 (30%) made by faculty members. The generated themes indicated that students and faculties found that dental education is going through a challenging time, because of the restrictions caused by the COVID-19 pandemic; and that they were aware about the evident division between basic/preclinical and applied/clinical courses. Faculties showed hopeful signs that the situation may get better. Students' drawings evoked the following topics: digital connectedness, diversity, time goes by, and future aspirations in Dentistry. Discussion This study reinforced the validity of visual methods as an approach in research and showed different graphical features (features that might be intentionally or unintentionally represented in the drawings) that gave voice to participants. These voices could have been invisible in more traditional qualitative approaches, such as interviews or questionnaires. Conclusions Although the two groups of participants came from different generation cohorts, they had aligned perceptions regarding challenges in dental education, and mentioned the separation between preclinic and clinic. Drawings were unique, innovative, and an interesting tool to express perceptions regarding today's learning environment. These insights can consequently help educators to personalize teaching approaches to better meet the needs of the students.